Implementation of the ITE Law and Democracy in Civil Space - Rona Indara; Albi Ternando (PT Inovasi Pratama Internasional, 2024)
The implementation of the ITE Law in general has not been implemented optimally , because the general public's understanding of the ITE Law is still imperfect, including community activities in cyberspace . Activities in cyberspace cannot be separated from human factors and their legal consequences also intersect with humans in society who are in the physical world, therefore the idea emerged about the need for legal rules to regulate activities in cyberspace. The word